Bimanual visually guided movements are more than the sum of their parts: Evidence from optic ataxia. Issue 7 (17th November 2019) - Litovsky, Celia; Yang, Feitong; Flombaum, Jonathan; McCloskey, Michael
ABSTRACT: Many reaching actions involve both hands. An open question is whether two-handed reaching involves two simultaneous, independent unimanual reaches, or recruits additional or different processes than those mediating one-handed reaching. We tested optic ataxic patient MDK on a set of unimanual and bimanual reaching tasks. Although MDK was impaired in both types of reaching task, his bimanual reaching was considerably better than his unimanual reaching. These results imply that bimanual reaching involves different or additional processes relative to unimanual reaching. We suggest that bimanual reaching may involve monitoring of the distance between the two hands relative to the distance between the two targets.